Application and effect evaluation of mouse and gastric injection 3D simulation model in medical experiment course - Zhai Lei; Zhong Ziyi; Hu Hua; Chen Mao (BIO Web of Conferences)
Purpose: This study aims to establish a 3D-printed mouse model with a gastric lavage needle, and to evaluate its improvement effect on students’ animal experimental gastric lavage operation. Methods: 106 students were randomly divided into two groups. The students in the experimental group used the model to practice gastric lavage operation before the formal experiment, and the control group did not use the model to practice gastric lavage operation before the formal experiment. The effectiveness of the last success rate, no complications and average gastric lavage time in the formal experimental course of the two groups was compared. Fruit. Results: In the formal experimental course, the first success rate: 86.54% in the experimental group, 22.22% in the control group; no complication rate: 96.15% in the experimental group, 81.48% in the control group; gastric irrhea time: experimental group: (17.02±1.51) S, control group: (38.85± 4.86) S, both of which are statistically significant. Conclusion: The application of 3D-printed mouse model with a gastric lavage needle exercises can improve the success rate and no complication rate of students’ gastric lava operation, and reduce the average gastric lavage time, which is in line with animal ethics and has certain economic benefits. It is worth promoting and use.